Wartime and Ukrainian Information Technology specialists’ wellbeing: exploring the role of internal resilience resources - Kryazh, Iryna; Kholmanova, Victoria (Psychology, Society & Education, 2024)
The Russian invasion of Ukraine in 2022 has significantly impacted the subjective well-being of Ukrainian Information Technology specialists, challenging their internal resilience resources, such as belief in a just world and existential fulfillment. This exploratory study investigates how wartime conditions influenced these professionals’ internal resources and subjective well-being. Two independent samples participated in two time points, 80 specialists in 2021, before the invasion (42.5% women; M = 35.33 years; SD = 7.77), and 77 in 2022, during wartime (48.05% women; M = 34.48; SD = 7.43). Moderation and mediation analyses were applied to examine the roles of personal belief in a just world, existential fulfillment, age, and gender. Findings reveal a considerable decline in subjective well-being and a weakening of internal resources, with the exception of the general belief in a just world. Age and gender as moderators modified changes induced by war in emotional discomfort and existential fulfillment, with decrease in the latter observed in two groups: women over 35 and men under 35. An increase in emotional discomfort was noted among women over 35. Mediation analysis showed that existential fulfillment and personal belief in a just world mediated the relationship between wartime stress and subjective well-being, as well as the effect of general belief in a just world on well-being. These results suggest that targeted support for maintaining existential fulfillment and personal belief in a just world may be essential for bolstering the well-being of Information Technology specialists under wartime conditions, particularly for vulnerable age and gender groups.